Muramyl Endopeptidase Spr Contributes to Intrinsic Vancomycin Resistance in Salmonella enterica Serovar Typhimurium - Vestö, Kim; Huseby, Douglas L.; Snygg, Iina; Wang, Helen; Hughes, Diarmaid; Rhen, Mikael (Frontiers in Microbiology, 2018)
The impermeability barrier provided by the outer membrane of enteric bacteria, a feature lacking in Gram-positive bacteria, plays a major role in maintaining resistance to numerous antimicrobial compounds and antibiotics. Here we demonstrate that mutational inactivation of spr, coding for a muramyl endopeptidase, significantly sensitizes Salmonella enterica serovar Typhimurium to vancomycin without any accompanying apparent growth defect or outer membrane destabilization. A similar phenotype was not achieved by deleting the genes coding for muramyl endopeptidases MepA, PbpG, NlpC, YedA, or YhdO. The spr mutant showed increased autolytic behavior in response to not only vancomycin, but also to penicillin G, an antibiotic for which the mutant displayed a wild-type MIC. A screen for suppressor mutations of the spr mutant phenotype revealed that deletion of tsp (prc), encoding a periplasmic carboxypeptidase involved in processing Spr and PBP3, restored intrinsic resistance to vancomycin and reversed the autolytic phenotype of the spr mutant. Our data suggest that Spr contributes to intrinsic antibiotic resistance in S. Typhimurium without directly affecting the outer membrane permeability barrier. Furthermore, our data suggests that compounds targeting specific cell wall endopeptidases might have the potential to expand the activity spectrum of traditional Gram-positive antibiotics.